2008
DOI: 10.1111/j.1939-1676.2008.0075.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Asymmetric Dimethylarginine, Symmetric Dimethylarginine, l‐Arginine, and Nitrite/Nitrate Concentrations in Cats with Chronic Kidney Disease and Hypertension

Abstract: Plasma ADMA and SDMA concentrations are increased in cats with CKD and correlate with plasma creatinine concentration. This may imply the presence of endothelial dysfunction in cats with CKD. Plasma ADMA concentrations were not associated with systemic hypertension. Treatment of systemic hypertension with amlodipine besylate did not affect plasma ADMA or NOx concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
56
1
7

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 39 publications
(45 reference statements)
5
56
1
7
Order By: Relevance
“…A significant positive correlation ( r = 0.72) was present between serum SDMA and sCr concentrations, similar to what has been reported previously in cats with CKD . These results support that SDMA is excreted primarily by the kidneys.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A significant positive correlation ( r = 0.72) was present between serum SDMA and sCr concentrations, similar to what has been reported previously in cats with CKD . These results support that SDMA is excreted primarily by the kidneys.…”
Section: Discussionsupporting
confidence: 90%
“…In another study using human subjects, a close correlation of GFR (measured by an iodothalamate clearance technique) with sCr and SDMA was reported ( r = −0.84 and −0.89, respectively) . Plasma SDMA concentrations also have been shown to be increased in cats with CKD and to correlate with plasma Cr concentration ( r = 0.74) …”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies have demonstrated a strong relationship between serum SDMA and creatinine concentrations . Serum SDMA concentrations increase above normal when GFR decreases by approximately 40% below the normal rate, much earlier than the 75% decrease in GFR typically required for creatinine concentrations to increase above reference limits .…”
mentioning
confidence: 94%
“…The cause has not been determined with certainty, but the effect may be endothelial dysfunction of which SDMA is believed to be a mediator . The vascular endothelium releases vasoactive substances such as nitric oxide (NO) which help maintain vascular integrity and regulate its homeostasis . Nitric oxide influences vascular tone, blood pressure, and regional blood flow while also having anti‐inflammatory, antithrombotic, and antiatherosclerotic effects .…”
mentioning
confidence: 99%